Burhoe's Second-Hand Influence - Cavanaugh, Michael (Zygon, 1998)
Many of us not part of the “old Burhoe gang” are nonetheless deeply influenced by the ideas of Ralph Wendell Burhoe, albeit in indirect ways. This remembrance summarizes six such ways: Three are “procedural” influences, namely (1) that dialogue is most valuable, especially in the science/religion interface, when carried on among those who may not agree; (2) that scholarship is necessary to refine and improve preliminary opinions; and (3) that organizations are crucial to accomplishing the first two tasks. The three “substantive” influences are (4) Burhoe's focus on human values; (5) his work in defining God; and (6) his contribution to defining what it means to be human. As is well known, his emphasis in all three substantive cases was on the power and nuances of biological and social evolution, especially on the dynamics of natural selection.